Ronda's Disease and Its Treatment: An Ethnomedical Study of the Kaili People in Palu City - Rismawati, Rismawati; Pageno, Isbon; Saifah, Andi (Journal of Health and Nutrition Research, 2025)
Ronda disease is a dermatological condition that often infects humans, causing symptoms like itching, skin pain, and prolonged fever. The Kaili ethnic group considers this disease dangerous and potentially fatal if not treated promptly. This study aimed to explore the Kaili community's perception of Ronda Disease. A qualitative method with a life history approach was employed to examine the community's knowledge and experience in seeking treatment. Data was collected through in-depth interviews with five purposively sampled informants: three patients with current or past Ronda Disease, one Sando (shaman), and one Sando assistant involved in treatment. Study results indicated that Ronda Disease is not viewed as an ordinary illness but as deliberately 'sent' to cause suffering. Two interviewed patients initially believed they had common skin conditions like eczema or athlete's foot; despite repeated consultations with dermatologists over several months, their condition did not improve. Following consultation with a Sando and a traditional diagnosis, they were identified as having Ronda Disease. Traditional treatment therapy, involving herbal concoctions and bathing rituals, was administered until recovery. These findings suggest that the modern health system faced challenges in adequately addressing this specific condition within this cultural context. Integrating modern and traditional health systems appears crucial for creating synergy in managing diverse health issues, including culturally specific conditions like Ronda Disease